2019
DOI: 10.1111/bcp.14064
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemotherapy drug wastage in a tertiary care hospital in India—A 3‐month prospective and 1‐year retrospective study

Abstract: This study prospectively quantified wastage of cancer chemotherapeutic drugs in an oncology unit to find the associated cost in 3 months. Retrospective analysis of drug usage for 12 months was also conducted to determine the expected drug loss in 1 year. The effect of vial sharing was evaluated under the assumption of sharing. A significant drug wastage of 19.72% (95% confidence interval [CI], 14.52-24.93%) in 3 months and 17.14% (95% CI 14.69-19.59%) in 1 year occurred in our oncology unit. Number of vials pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
(9 reference statements)
3
16
1
Order By: Relevance
“…Nonetheless, the study has demonstrated substantial cost savings due to vial-sharing, which supports other studies that encourage the use of vial-sharing to reduce chemotherapy wastage. 9,12,25…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the study has demonstrated substantial cost savings due to vial-sharing, which supports other studies that encourage the use of vial-sharing to reduce chemotherapy wastage. 9,12,25…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study found the cost of chemotherapy wastage to be 17.14% of the total expenditure on drugs in 1 year. 9 The cost savings generated from addressing chemotherapy wastage can be diverted to improve patients’ access to novel chemotherapy drugs and enhance patient care, therefore highlighting the need to reduce chemotherapy wastage. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures for drug wastage are one of the most important strategies for containing this cost. One of the most common causes of drug wastage is the discarding of residual anticancer drugs after preparation . Application of dose rounding of chemotherapy to the nearest vial size and drug vial optimisation, which allows the use of single‐use vials for multiple patients, are effective measures for minimising leftover anticancer drugs …”
Section: Discussionmentioning
confidence: 99%
“…One of the most common causes of drug wastage is the discarding of residual anticancer drugs after preparation. 8 Application of dose rounding of chemotherapy to the nearest vial size and drug vial optimisation, which allows the use of single-use vials for multiple patients, are effective measures for minimising leftover anticancer drugs. 4,9,10 However, in our hospital, there were 18 cases (18 patients) in 2016 (before introduction of the present protocol) in which anticancer drugs were discarded after preparation.…”
Section: Discussionmentioning
confidence: 99%